Pengembangan Sumber Daya Manusia dalam Meningkatkan Kualitas Kinerja Tenaga Pendidik dan Kependidikan di SMA Muhammadiyah 1 Ponorogo - Hardaning, Novita Kusuma; Yahya, Fata Asyrofi (Letiges, 2021)
This research discusses the development of educators and education staff which aims to determine the quality of performance carried out whether it has increased or not. Schools need to develop educators and education personnel to improve quality and ability through development activities such as training, career development, and motivation so that the success of human resource development can be determined. This research uses a case study approach with qualitative research, the methods used are interviews, observation, and the use of documents as data collection. The results of the research show that the form of development that has been carried out by the school is by providing various training that has been planned, then through gradual career development planning and in accordance with the tenure, and through providing motivation to all human resources. Then the success of the development can be seen through improving the performance of each human resource, through performance appraisals carried out by the principal and his representatives and paying attention to predetermined performance indicators.